Analysis of Employee Development Strategies to Improve Skills and Motivation in the Company - Erfan, Muhammad; Bakri, Muhammad (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study explores the effectiveness of employee development strategies in enhancing workforce skills and motivation, particularly in the context of digital transformation and evolving work environments. It integrates training methodologies, career development initiatives, and motivation theories to provide a holistic framework for sustainable workforce growth. The study also identifies differences in strategy implementation between large corporations and small and medium-sized enterprises (SMEs), addressing key challenges and opportunities in employee development. Research Method: This research employs a Systematic Literature Review (SLR) approach, synthesizing peer-reviewed journal articles and scholarly sources from Elsevier, Emerald, Wiley, and Springer published after 2018. The methodology involves structured data extraction, thematic categorization, and critical analysis to assess trends in training effectiveness, motivation, and career development strategies. By systematically reviewing recent empirical and theoretical studies, this research presents a comprehensive synthesis of the latest insights on employee development. Results and Discussion: The findings highlight that technology-driven training, mentoring, and structured learning initiatives have a significant impact on improving employee competence and motivation. A balance between intrinsic and extrinsic motivation is essential for sustaining engagement and retention. The study also underscores the impact of digitalization, necessitating adaptive workforce training models. Differences in strategy implementation between large firms and SMEs reveal that while large corporations benefit from structured development programs, SMEs can leverage alternative strategies such as community-based training and collaborative skill-building initiatives. Implications: This research provides practical insights for business leaders and HR practitioners, emphasizing the importance of data-driven, flexible, and technology-integrated employee development strategies. It also offers policy recommendations for supporting workforce upskilling in response to rapid industry changes. Future research should explore sector-specific workforce development models and empirically validate these strategies in diverse organizational settings.